DETERMINAN RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI ISSI (STUDI PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS SAHAM SYARIAH 2016 - 2018) - APRILLIA .; JMV MULYADI; NURMALA AHMAR (LP2MTBM MAKARIOZ, 2021)
The purpose of this study is to test empirical evidence related to the analysis of return on asset (ROA), Curent Ratio (CR),Debt to Equity Ratio (DER) and Earning Per Share (EPS) relationships to manufacturing companies incorporated in theIndonesia Sharia Stock Index (ISSI) on the Indonesia Stock Exchange for the period 2016-2018. The necessary datacollection method is collected using documentation techniques (desk research), with a sample number of 32 companies. Thedata analyzed in the study was compiled from the company's annual reports and financial statements. The analyticaltechniques used are descriptive analysis and panel data with SPSS programs. The results showed that curent ratio (CR),and debt to equity ratio (DER) have a positive and significant effect on stock returns, return on assets (ROA) and earningsper share (EPS) have no effect on stock returns.